Sosialisasi Pemanfaatan Kelapa Menjadi Virgin Coconut Oil Sebagai Upaya Pengembangan UMKM Berbasis Potensi Lokal di Desa Ariate - Isak P Siwa; Hengki A Samar; Ridwan A Pelu; Faradika Ramadhani Tohalo; Juliet A Rering; Nilam Cahya (Takuana: Jurnal Pendidikan, Sains, dan Humaniora, 2026)
Coconut is one of the leading plantation commodities in Ariate Village, Huamual District, West Seram Regency. However, its utilization is still limited to selling whole coconuts and copra, resulting in relatively low economic value. This community service activity aimed to increase public knowledge regarding the utilization of coconuts into Virgin Coconut Oil (VCO) and to introduce opportunities for developing local potential-based Micro, Small, and Medium Enterprises (MSMEs). The activity was conducted through participatory socialization involving 11 participants consisting of housewives, coconut farmers, and members of the Ariate Village community who were interested in learning about coconut processing as a value-added product. The methods used included pre-test, material presentation, brochure distribution, product introduction, discussion, and post-test. VCO was produced using a natural fermentation method as a demonstration product during the activity. The results showed a significant improvement in participants’ understanding of VCO. The percentage of participants who understood the definition, benefits, and production process of VCO increased from 18.18% before the activity to 100% after the socialization. Therefore, the activity successfully enhanced community knowledge and promoted the utilization of coconut as a value-added product to support local MSME development in Ariate Village.